HUBUNGAN SIKAP DENGAN TINGKAT KECEMASAN REMAJA PUTRI KELAS V MENJELANG MENARCHE DI SDN KANDANG SAPI II KOTA PASURUAN - Zainuri, Imam; Mardiana, Ella (JURNAL KEPERAWATAN BINA SEHAT, 2012)
First menstruation, or menarche is a natural thing that must be experienced by every normal woman who do not have troubled. However this will only get worse if the knowledge of adolescents about the menstrual period is very less and the education of the parents is lacking, so that early adolescents have less knowledge and a fairly good attitude and causes of feelings of anxiety and fear will emerge. The purpose of this study was to analyze the corelation attitude of young women with anxiety levels before menarche class V in SDN Kandangsapi II Pasuruan. Design of the study is correlational analytic with cross sectional approach. Population are all young women fitfth grade in SDN Kandangsapi II Pasuruan that before menarche, amounting to 33 students with a total sampling technique to obtain a sample of 33 students. Independent variables is the attitude and the dependent variable young women anxiety levels before menarche fitfth grade. Data is taken with a questionnaire and analyzed by spearman rho test statistics. The results showed 19 positive respondents who obtained 16 (84.2%) of them have medium anxiety levels and the remaining three (15.8%) severe anxiety levels. The results of statistical tests of significance sebesat obtained value 0.002 <α (0.05) so H0is rejected. From the results of research and statistical test known to have corelatoin the attitude of young women with anxiety levels before menarche fitfth grade. The informations which are founded will certainly influence young women’s attitude, their positiv or negativ attitude certainly will also influence their anxiety level in facing the menarche.Key words: attitudes, anxiety, menarche